Prototipe Sistem Pendeteksi Banjir Berbasis IoT (Internet Of Things) (UNISTEK, 2022)
Flood is one of the natural disasters that often occur in Indonesia. The amount of loss caused by the flood is immeasurable. This is also felt by residents of Cimone Mas Permai 2 Housing Estate, Tangerang City. Every rainy season, it is certain that they are always affected by floods. Therefore, an effort is needed to minimize the possibility of losses received by making a prototype of a flood detection system to monitor the height and swiftness of the water flow. This system is based on the Internet of Things (IOT), which is a network that connects various physical devices with their respective protocols. This flood detection system uses a waterflow sensor to calculate the speed of water flow, a Water Level sensor as a water level detector, Arduino Uno as a value center for various sensors, Nodemcu ESP8266 as a sender of sensor values to the Firebase database. The system will operate directly when given power and read each sensor which will be sent to the database. Residents will get information about flood heights through an Android application that is connected to internet data. And admins can monitor assistance reports from the admin website. Keywords : Arduino Uno, Waterflow Sensor, Water Level Sensor, Android